2019
DOI: 10.3389/fmicb.2019.02685
|View full text |Cite
|
Sign up to set email alerts
|

Minor Effect of Antibiotic Pre-treatment on the Engraftment of Donor Microbiota in Fecal Transplantation in Mice

Abstract: Fecal microbiota transplantation (FMT) is an effective therapy for recurrent Clostridioides difficile infection (rCDI) and is also considered a potential treatment for a wide range of intestinal and systemic diseases. FMT corrects the microbial dysbiosis associated with rCDI, and the engraftment of donor microbiota is likely to play a key role in treatment efficacy. For disease indications other than rCDI, FMT treatment efficacy has been moderate. This may be partly due to stronger resilience of resident host … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 41 publications
0
45
0
Order By: Relevance
“…However, few experimental and clinical studies have addressed the contribution of antibiotic pre-conditioning before FMT to donor microbiota engraftment efficacy and results are still contradictory. For instance, Freitag et al, have observed that pre-treatment with antibiotics did not improve the engraftment of donor microbiota, but did improve the engraftment of specific bacteria in the context of Clostridium infection [34]. By contrast, Le Roy et al observed that pre-treated groups (with laxatives or antibiotics) harbored a significantly better engraftment and phenotype in context of obesity [27].…”
Section: Discussionmentioning
confidence: 99%
“…However, few experimental and clinical studies have addressed the contribution of antibiotic pre-conditioning before FMT to donor microbiota engraftment efficacy and results are still contradictory. For instance, Freitag et al, have observed that pre-treatment with antibiotics did not improve the engraftment of donor microbiota, but did improve the engraftment of specific bacteria in the context of Clostridium infection [34]. By contrast, Le Roy et al observed that pre-treated groups (with laxatives or antibiotics) harbored a significantly better engraftment and phenotype in context of obesity [27].…”
Section: Discussionmentioning
confidence: 99%
“…Ongoing debate exists regarding the pre-treatment of recipients with antibiotics prior to FMT to increase efficacy [ 71 , 72 ]. Conceptually, antibiotic pre-treatment helps provides a proverbial ecological clean slate for the engraftment of donor microbes by freeing up otherwise occupied niches.…”
Section: Discussionmentioning
confidence: 99%
“…As rCDI patients usually have aberrant and less abundant gut microbiota, it might provide bifidobacteria with niches not necessarily present in healthy microbiota. Indeed, a recent mouse study demonstrated that antibiotic pre-treatment prior to FMT enhances specifically the colonization of bifidobacteria (Freitag et al, 2019). In this study, all the recipients were rCDI patients who had received multiple antibiotic treatments before FMT, which may have contributed to the observed colonization of bifidobacteria.…”
Section: Discussionmentioning
confidence: 80%